2018
DOI: 10.1186/s12889-018-6046-9
|View full text |Cite
|
Sign up to set email alerts
|

MHealth approach to promote Oral HIV self-testing among men who have sex with men in China: a qualitative description

Abstract: BackgroundHIV self-testing (HIVST) has demonstrated potential to expand HIV testing among key populations, including men who have sex with men (MSM) in China who have low testing rates. However, due to the autonomous nature of self-testing, people who undergo HIVST may lack access to relevant information and counseling support typically provided by in-person HIV testing counselors. WeChat, a popular smartphone application in China, offers a potential source of mobile health (mHealth) information and support fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 35 publications
5
43
0
Order By: Relevance
“…Our results showed that HIVST Users had a higher frequency of gay apps use than Non-HIVST users in the prior 6 months. As with previous ndings, the utility of mobile health interventions can engage MSM in HIVST in Heifei and Shenzhen, China 27,28 , and increase rates of con rmed HIV diagnoses and linkage to clinical care in the UK 29 . Furthermore, consistent with ndings in other studies 22 , those who had high-risk sex behavior, including multiple male sex partners, frequency of male-male sexual contact more than once per week and syphilis infection were more likely to have had HIVST.…”
Section: Discussionsupporting
confidence: 67%
“…Our results showed that HIVST Users had a higher frequency of gay apps use than Non-HIVST users in the prior 6 months. As with previous ndings, the utility of mobile health interventions can engage MSM in HIVST in Heifei and Shenzhen, China 27,28 , and increase rates of con rmed HIV diagnoses and linkage to clinical care in the UK 29 . Furthermore, consistent with ndings in other studies 22 , those who had high-risk sex behavior, including multiple male sex partners, frequency of male-male sexual contact more than once per week and syphilis infection were more likely to have had HIVST.…”
Section: Discussionsupporting
confidence: 67%
“…Based on the IMB model of HIV behavior change [28], an initial formative study sought to characterize information domains, motivational factors, and behavioral facilitators to promote HIVST and behavioral risk reduction in the target group. We conducted indepth individual interviews to explore prospective users’ preferences with respect to content of HIVST promotion and HIV prevention messages delivered via WeChat [29]. Based on analysis of qualitative data, an interdisciplinary research team worked in collaboration with staff from a community-based, MSM-focused, HIV prevention organization in Hefei to create a library of messages to provide information, motivation, and behavioral recommendations regarding the need for regular HIV testing and condom use among MSM.…”
Section: Wetest Intervention Developmentmentioning
confidence: 99%
“…Most men, including a substantial number of firsttime testers, claimed the app gave them a "nudge" to test for HIV. Other studies have shown the potential of a digital intervention to support early HIV diagnosis in men (Rawat et al, 2018;Wood et al, 2019;Zhao et al, 2018). However, individuals' autonomy to test for HIV was shaped by factors other than the app, suggesting that digital applications like EPIC-HIV1 may be most effective for men when used to support effective decentralised HIV care (Li et al, 2017;Liu et al, 2016;Nakanwagi et al, 2016;Nhassengo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Digital interventions such as mobile communication technologies (mHealth) have the potential to fill this health promotion gap and support men's engagement with HIV care (Adeagbo et al, 2019). The World Health Organization has recommended the use of mHealth for HIV and other chronic disease management (Daher et al, 2017;WHO, 2011;Zhao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%